A new strategy in bioreactor scale-up and process transfer using a dynamic initial vvm according to different aeration pore size - Ding, Huaping; Cheng, Huanghe; Wu, Jiaxian; Zhang, Fan; Cao, Can; Mualif, Siti Aisyah; Xie, Zhenggang (Frontiers in Bioengineering and Biotechnology, 2024)
Monoclonal antibody drugs have grown into a drug category with a market size of over $100 billion since the first product was launched on the market, which naturally creates a large demand for production. At the same time, the $100 billion market is distributed among more than 200 listed drugs, which indicates that the production demand for monoclonal antibody drugs is diverse. To meet this demand, major suppliers offer single-use bioreactors of all sizes. These single-use bioreactors with different specifications, especially the inconsistency of aeration pore sizes, pose great challenges for technology transfer and scale-up production, and the conventional scale-up strategies of constant Power input/volume ratio (P/V) and constant vessel volume per minute (vvm) can no longer meet the needs. This study simplified the selection of technical parameters in bioreactors based on the differences in aeration pore size. Innovatively combined the aeration pore sizes with initial aeration vvm, and comprehensively investigated the relationship between P/V, vvm and aeration pore size by designing experiments (DoE) using the orthogonal test method. The results showed a quantitative relationship between the aeration pore size and the initial aeration vvm in the P/V range of 20±5 W/m 3 . The appropriate initial aeration was between 0.01-0.005 m 3 /min for aeration pore size ranging from 1 mm to 0.3 mm, which was the optimal incubation condition in the bioreactors. The choice of initial ventilation was